Membangkitkan Kesadaran Kerajaan Allah di Kalangan Generasi Muda - Kobstan, Heintje Barry; Sanger, Beby Kezia (STT KINGDOM BALI, 2025)
The Kingdom of God is a government in which God is fully sovereign as King who rules over His people. This Gospel of the Kingdom is what Jesus preached and taught during His time on earth, to make people aware that in this world system that is corrupted by sin, the Kingdom of God comes by declaring a new government that is different from the governments of the world. Unfortunately, there are still many Christians who have believed and been born again but have not realized or fully understood this Gospel of the Kingdom, including the younger generation. The purpose of this study is to find ways to foster awareness of the Kingdom of God, especially in the younger generation who are living in this modern era.